The Effect of User Experience and System Responsiveness on the Continued Use of the Livin’ by Mandiri Application among Students of the Faculty of Economics, Universitas Negeri Jakarta, with User Satisfaction - Jauza Aqhna Kamila; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study examines how User Experience and System Responsiveness influence the continued use of the Livin’ by Mandiri application among students of the Faculty of Economics at Universitas Negeri Jakarta, with User Satisfaction serving as a mediating variable. The research employs a quantitative approach, and the data are analyzed using Structural Equation Modeling (SEM) with the assistance of the SmartPLS software. The participants in this study are active students from the Faculty of Economics, Universitas Negeri Jakarta, who actively use the Livin’ by Mandiri application. The results demonstrate that User Experience and System Responsiveness both have a positive and significant impact on User Satisfaction. Furthermore, User Experience and User Satisfaction significantly contribute to the continued use of the application. However, System Responsiveness does not show a significant direct influence on continued use. The mediation analysis further indicates that User Satisfaction partially mediates the relationship between User Experience and continued use, while it does not mediate the relationship between System Responsiveness and continued use. These findings highlight the critical role of user satisfaction in encouraging the sustained use of digital banking applications over time.